Lugar afetivo: possibilidades de pensar a imagem na produção artística contemporânea - Vesz, Jessica Anibale (2020)
Located in the field of Visual Arts, the research encompasses a study developed in Visual Poetics, which is elaborated with reference in a specific place, understood as an affective place. The practical development, configured in the artistic production resulting from the research, is carried out through photographic and videographic images, generating reflections about the “temporal multiplicities”, originating from that specific space. This concept is elaborated, mainly, according to the approach of Gilles Deleuze and Félix Guattari (1997). The images generated portray the particularities inherent to the object of study, brought from the audiovisual and photographs of the chosen location (a wood sawmill), as well as the relationship between object / image based on the concept of “index” proposed by Phillipe Dubois (2010). In this process, we seek to investigate how the image as a driving element of poetics can provide reflections and artistic productions based on that affective place, aiming at the constitution of proposals in Art and Technology. Therefore, it articulates around the purpose of reframing such a space, due to experiences and personal experiences, transposing it to a production in Art, with Poiética (REY, 2002) as a theoretical corpus. In this context, certain criteria are established, such as the use of logbooks, verbalizations about the research and search for artistic references, in order to establish dialogues that help to understand the context of current manifestations, based on the guidelines developed throughout the research. Thus, a diverse set of productions is generated, audiovisual as well as printed, and objects which encompasses the issues raised throughout the investigation, proposing reflections on the theme and chosen processes.